Pendampingan Pembuatan dan Pengelolaan Akun Bisnis Media Sosial untuk Penetrasi Pasar: Assistance in Creating and Managing Social Media Business Accounts for Market Penetration - Agustino, Muhammad Rizqi; Citrapati, Mugito; Saputra, Muhammad Yoga Aditya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The low market penetration and narrow market reach have limited the development and growth of UMKM Batik Sekar Rinambat. This community service aims to enhance and develop UMKM’s ability to penetrate and expand the market. The method involves providing intensive assistance in several stages, including mindset changes, behavioral adjustments to be open to technology facilities and features, and direct practice and implementation. The target of this service includes business accounts, business pages, and proof of marketplace usage on one of the social media platforms used. It is hoped that this will provide a wider market potential.